Social Networking analysis (SNA) no futebol - observação e análise das ligações interpessoais das equipas adversárias - Carlos Manuel Monteiro Mendonça (2016)
Football is a collective sport where 22 players interact with the aim of introducing the ball in the opponent's goal and prevent the opponents to do the same in yours. That is a sport of cooperation/opposition where it becomes important to analyze this set of forces to reduce the randomness and unpredictability. Increasingly scouting departments, through its observers and analysts, try to understand these interactions using various techniques and tools. The aim is to try to reduce the unpredictability by detecting patterns and indicators to systematize and characterize the collective dynamics in a competitive context. The Social Network Analysis (SNA) applied to soccer, allow us to obtain quantitative values on this collective dynamics over the performance of individual players. This report was organized as part of the conclusion of studies in the 2nd cycle in High Performance Sports on the Sports Faculty of the University Porto (FADEUP), spreading the experiences and knowledge gained in the course of the season 2015/16 in the professional team soccer, Clube de Futebol União da Madeira, that attended the Portuguese First Division. It is intended with this report, to demonstrate the importance of the emergence of new mechanisms and techniques of observation and game analysis, especially the interaction and relationship between field players through network analysis. In order to complement the observation report and analysis of the opposing team, it was prepared a weekly report of the last game played with TV broadcast. It was intended with this tool, to give more information and make it more visually perceptible to coaches, so they can make adjustments of the playing style and their training process in order to combat or support its strategies or game ideas. The SNA has proven to be an important tool for the further study of the collective dynamics arising from cooperation and opposition situations between players.